Efektivitas Program Promosi Produk Halal dalam Pemberdayaan Ekonomi Umat: Studi Kasus Kampanye Dakwah Digital - M Gustar Umam; Muhamad Zen; Fatmawati, Fatmawati (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The Strategic Role of Halal Products in Empowering the Muslim Economy Halal products play a strategic role in empowering the Muslim economy, especially in Muslim-majority countries like Indonesia. This article aims to analyze the effectiveness of promoting halal products through digital da'wah approaches, branding strategies, and halal regulations in driving the growth of the halal industry and empowering the Muslim economy. The use of social media as a means of digital da'wah has proven effective in raising public awareness about the importance of consuming halal products. Halal branding strategies that leverage certification, Islamic imagery, and sharia-compliant marketing communication have successfully built consumer loyalty and increased product competitiveness in the global market. Furthermore, the implementation of halal regulations—particularly Indonesia's Halal Product Assurance Law provides a strong legal foundation for the development of the halal industry. Case studies from halal cosmetic brand Wardah and several MSMEs show that digital transformation accelerates market penetration and operational efficiency in halal businesses. This article concludes that the integration of digital da'wah campaigns, branding strategies, supportive regulations, and digitalization of the halal industry significantly contributes to the growth of sharia-compliant businesses and the economic well-being of the Muslim community. Recommendations are offered to industry players, policymakers, and the public to strengthen the halal ecosystem through continuous collaboration and innovation.